2014
DOI: 10.1021/jp412463v
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Self-Assembly of Nanostructured CuSCN/Rhodamine B Hybrid Thin Film and Its Dye-Sensitized Photocathodic Properties

Abstract: Nanostructured hybrid thin films of CuSCN and rhodamine B (RB) are electrochemically self-assembled (ESA) by cathodic electrolysis in an ethanol/water mixture containing Cu2+, SCN–, and RB. By selecting the solvent, Cu2+/SCN– ratio, and the concentration of RB, we demonstrate several control parameters in the film formation. High loading of RB into the film has been achieved to reach a CuSCN:RB volume ratio of approximately 2:1. The RB solid could almost completely be extracted from the hybrid film by soaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…As presented in Figure 1 a, CuSCN thin films exhibit smooth and continuous surface (with a RMS roughness of 7.5 nm) composed of nanocrystalline domains. The XRD pattern (Figure b) of distinct peaks at 2 θ = 16.1°, 27.2°, 30.3° are corresponding to the typical diffractions of (003), (101), (012) planes, revealing the formation of rhombohedral phase (β‐phase) in CuSCN thin films . Figure c shows light absorption of CuSCN and PEDOT:PSS thin films at the same thickness.…”
Section: Methodsmentioning
confidence: 97%
“…As presented in Figure 1 a, CuSCN thin films exhibit smooth and continuous surface (with a RMS roughness of 7.5 nm) composed of nanocrystalline domains. The XRD pattern (Figure b) of distinct peaks at 2 θ = 16.1°, 27.2°, 30.3° are corresponding to the typical diffractions of (003), (101), (012) planes, revealing the formation of rhombohedral phase (β‐phase) in CuSCN thin films . Figure c shows light absorption of CuSCN and PEDOT:PSS thin films at the same thickness.…”
Section: Methodsmentioning
confidence: 97%
“…Electrodeposition-based methods have been shown to be able to tune the orientation between the (001)-terminated and (101)-terminated surfaces [(001) or (101) planes parallel to the substrate surface, respectively, ( Figure 5)]. [45,46] Although for solution-grown CuSCN films the evidence is not yet clear due to the often small layer thicknesses, results also indicate the presence of (101) or (001) surface-oriented crystals. [11,33] Computational results suggested that the (101)-and (001)-orientations of hexagonal β-CuSCN could be stable especially when terminated with Cu, but the most stable surfaces were (100) and (110).…”
Section: Surfaces Of Cuscnmentioning
confidence: 99%
“…Cathodic electrodeposition of CuSCN thin films has already been well established and understood. 9,11,16,23 A 1:1 complex between Cu 2+ and SCN – ions, denoted as [Cu(SCN)] + , is spontaneously formed by dissolving equal molar amounts of Cu(ClO 4 ) 2 and LiSCN in alcohol such as methanol and ethanol. This complex is the active species to be reduced at the electrode to precipitate CuSCN with a Faradic efficiency of practically 100%.…”
Section: Resultsmentioning
confidence: 99%
“…17 Indeed, dye-sensitized photocathodic current was observed for a porous CuSCN sensitized with RB. 9…”
Section: Introductionmentioning
confidence: 99%